TESL trainee teachers’ workplace competencies (English language skills) and the workplace expectations / Nurdiyana Mohamad Yusof, Marina Mohd Arif and Fatin Aliana Mohd Radzi - Yusof, Nurdiyana Mohamad; Mohd Arif, Marina; Mohd Radzi, Fatin Aliana (Universiti Teknologi MARA, Kedah, 2024)
Malaysia recognizes the crucial role of English as a global language, especially in driving economic growth and technological development. While the government has made efforts to improve English proficiency, concerns persist about the language skills of students and graduates. Recent initiatives have emphasized the importance of English competency assessments, particularly for civil servants. However, a significant gap remains between the English language proficiency required by industries and the skills demonstrated by graduates, especially those from non-English programs. This study focused on assessing the English language proficiency of TESL trainee instructors. Through interviews with English teachers and classroom observations aligned with CEFR standards, the study found that most TESL trainees are rated as proficient in English and express confidence in their teaching abilities. These findings align with the government's goal of enhancing English proficiency among teachers. However, the study also suggests that there is room for improvement in TESL teacher training programs to ensure that graduates are equipped with the necessary skills to effectively teach English in Malaysian schools.